2000
DOI: 10.1097/00007632-200012010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Tumor Necrosis Factor-Alpha Mimics Nucleus Pulposus-Induced Neuropathology

Abstract: The data reinforce other evidence that tumor necrosis factor-alpha is involved in mechanisms of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(106 citation statements)
references
References 24 publications
1
104
1
Order By: Relevance
“…The capacity of normal disc cells to secrete proinflammatory cytokines and interleukin-10 in the absence of inflammatory cells was observed in cultured murine disc [28]. TNF-a is spontaneously produced by intervertebral disc tissue in culture, and it has been found in the NP cells of rats and pigs [8,18,27]. In herniated disc, TNF-a is expressed at higher levels compared to asymptomatic or autopic controls [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of normal disc cells to secrete proinflammatory cytokines and interleukin-10 in the absence of inflammatory cells was observed in cultured murine disc [28]. TNF-a is spontaneously produced by intervertebral disc tissue in culture, and it has been found in the NP cells of rats and pigs [8,18,27]. In herniated disc, TNF-a is expressed at higher levels compared to asymptomatic or autopic controls [29].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, known as hyperalgesia, is a common denominator of all inflammatory processes and is characterized by the decrease in the nociceptive threshold and increased activity in response to thermal and mechanical stimulation [15]. The role of local cellular mediators such as cytokines and chemokines in the inflammatory hyperalgesia was extensively studied and there is no doubt nowadays about their involvement in the etiology of the painful sensitization after tissue damage [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The role of TNF-a in animal models of sciatica has been documented [32]. Furthermore, Olmarker and Rydevik [33] reported the efficacy of TNF-a in preventing NP-induced functional and structural nerve root injury in animal models.…”
Section: Tumor Necrosis Factor-alpha (Tnf-a) Blockadementioning
confidence: 99%
“…It is suggested that the cytokine known as tumour necrosis factor a (TNFa) may be a significant player in this pathway [10]. Indeed, antibodies to TNFa are being used in clinical trials with encouraging results [11].…”
Section: Introductionmentioning
confidence: 99%